PREVALENCE AND FACTORS ASSOCIATED WITH IRON DEFICIENCY ANEMIA IN PEDIATRICS IN SICKLE CELL PATIENTS IN THE INTERCRITICAL PHASE IN THE DR CONGO - John-Peter, Mulindwa Murhula; Fortune, Cimanya Chubaka Fortune; Phillipe, Amani Busane; Christian, Bulonza Mushobekwa; Eric, Amani Lubunga; Marie, Maerevoet; Archippe, Birindwa Muhandule (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Introduction: Homozygous sickle cell disease in the DR Congo is the most common hemoglobinopathy. Sickle cell disease is manifested by a regenerative anemia whose severity varies greatly depending on the individual. Sickle cell syndromes probably lead to inflammation and iron balance disorders. The objective of this study is to improve management by determining the prevalence of iron deficiency anemia and to study the factors associated with this anemia in sickle cell patients in the inter-critical phase. Method: This is a comparative and analytical study carried out in two hospitals in the city of Bukavu, the Panzi General Reference Hospital and the Ami des Enfants clinic, over a period of one year, from September 1, 2023 to September 31, 2024. This study involved 68 sickle cell anemic patients, of whom 38 had iron deficiency anemia taken as cases and 30 without iron deficiency anemia taken as controls. The inclusion criteria are: being sickle cell in the inter-critical phase, anemic (hb < 11g / dl). Logistic regression allowed us to identify the factors associated with this iron deficiency anemia in sickle cell patients. Results: out of 68 sickle cell anemic patients, 38 had iron deficiency anemia, a prevalence of 55.9%, the average age was 7.8±3.9 years, with a male predominance (65.2%), sex was a factor significantly associated with iron deficiency anemia (OR: 5.2 p: 0.002). Primary school level (47%) was also associated with this iron deficiency anemia (OR: 0.4p: 0.02). Clinically, the factors associated with iron deficiency anemia were the average age of diagnosis of the pathology, i.e. 6.4±3.7 years, (t: 2.1 p: 0.02). The average number of hospitalizations was 4.9±5.5 times, with a significant difference to controls (t: 1.1, p: 0.04). Biologically, the mean hemoglobin level of the cases 6.8±1g/dl was not far from that of the controls i.e. 6.96±1.6 g/dl, their anemia was microcytic at 16% and macrocytic at 8%. The quantitative CRP, its mean is on the other hand very high in the controls i.e. 25.8±30 mg/l against 9±12.6 mg/l (t: -3.5 p: 0.003). The mean ferritin in the cases was 59.6±30.1 ng/l. Hemoglobins A and F of sickle cell patients show that in cases the average Hb A is zero and HbF is 13±7%, and in controls, the average HbA is 2±6ng/l and HBF is 18±7ng/l. The average number of transfusions was equal in cases and controls, i.e. 2.5±2.5 transfusions. Conclusion: Iron deficiency anemia has a high prevalence in sickle cell patients, several factors including sociodemographic, clinical and biological remain associated with this anemia even in the inter-critical phase.